Most patients are eligible for an alternative to conventional whole breast irradiation for early‐stage breast cancer: A National Cancer Database Analysis. Issue 5 (20th May 2018) - Balagamwala, Ehsan H.; Manyam, Bindu V.; Leyrer, Charles Marc; Karthik, Naveen; Smile, Timothy; Tendulkar, Rahul D.; Cherian, Sheen; Radford, Diane; Al‐Hilli, Zahraa; Vicini, Frank; Shah, Chirag
Abstract: We evaluated the proportion of patients eligible for alternatives to standard whole breast irradiation (WBI) following breast‐conserving surgery using the National Cancer Database (NCDB). Using the 2016 dataset, Stage I‐III patients were identified. Eligibility for hypofractionated WBI (HFRT), accelerated partial breast irradiation (APBI) and endocrine therapy (ET‐alone) was defined using eligibility from large clinical trials as well as consensus guidelines. For patients with pN0 breast cancer, 20.6% and 37.0% were eligible for ET‐alone based on the CALGB 9343/PRIME‐II trials, respectively. In terms of HFRT, 72.5% and 50.4% were eligible based on IMPORT LOW/ASTRO HFRT guidelines, respectively. Based on IMPORT LOW/GEC‐ESTRO trial/ASTRO guidelines/ABS guidelines/GEC‐ESTRO guidelines, 72.5%, 86.1%, 39.0%, 72.5%, 45.7%, respectively, were eligible for APBI. Of those who qualify for HFRT per ASTRO guidelines, approximately 90% were eligible for APBI and 50% for ET‐alone. This analysis shows that a large proportion of patients with node‐negative breast cancer are eligible for HFRT, APBI and/or ET‐alone after breast‐conserving surgery.